2006
DOI: 10.1111/j.1439-0388.2006.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of single‐nucleotide polymorphisms in 5′ end and exons of the PRKAG3 gene in Hubbard White broiler, Leghorn layer, and three Chinese indigenous chicken breeds

Abstract: 5'-AMP-activated protein kinase plays an important role in regulating the level of ATP in the presence of metabolic stress. Previous studies revealed that polymorphisms in 5'-AMP-activated protein kinase gamma 3 subunit (PRKAG3) gene are associated with meat quality in pigs. In the present study, single-nucleotide polymorphisms (SNPs) in the 5'-end and exons of chicken PRKAG3 gene were identified with the method of single-strand conformation polymorphism in Hubbard ISA White broiler, Leghorn layer, and three C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…No SNP was detected in the corresponding position as observed in the porcine gene that caused the R225Q mutation (Zhao et al, 2006). Mutations at positions 2720 and 2786 of the cPRKAG3 gene were located in sequence corresponding to the fourth CBS domain of human PRKAG3 (Zhao et al, 2006). Additionally, an allele frequency study indicated that among the five chicken breeds, Leghorn layers have the least number of polymorphisms at the cPRKAG3 gene locus (Zhao et al, 2006).…”
Section: Ampk Subunit Gene Structure and Genomic Organizationmentioning
confidence: 92%
See 4 more Smart Citations
“…No SNP was detected in the corresponding position as observed in the porcine gene that caused the R225Q mutation (Zhao et al, 2006). Mutations at positions 2720 and 2786 of the cPRKAG3 gene were located in sequence corresponding to the fourth CBS domain of human PRKAG3 (Zhao et al, 2006). Additionally, an allele frequency study indicated that among the five chicken breeds, Leghorn layers have the least number of polymorphisms at the cPRKAG3 gene locus (Zhao et al, 2006).…”
Section: Ampk Subunit Gene Structure and Genomic Organizationmentioning
confidence: 92%
“…They found 12 potential SNPs (ten in exons 3, 4, 9 and 11, and two in 5 0 -end sequence), but only three of them resulted in amino acid substitutions (Zhao et al, 2006). No SNP was detected in the corresponding position as observed in the porcine gene that caused the R225Q mutation (Zhao et al, 2006). Mutations at positions 2720 and 2786 of the cPRKAG3 gene were located in sequence corresponding to the fourth CBS domain of human PRKAG3 (Zhao et al, 2006).…”
Section: Ampk Subunit Gene Structure and Genomic Organizationmentioning
confidence: 95%
See 3 more Smart Citations